Alterations in whole muscle quality and physiological cross-sectional area measured with quantitative MRI following ACL injury - Meredith K. Owen; Lauren Richardson; Darren L. Johnson; Moriel H. Vandsburger; Thorsten Feiweier; Katherine L. Thompson; Christopher S. Fry; Peter A. Hardy; Brian Noehren (Journal of Translational Medicine)
Abstract Background Emerging evidence suggests that there are morphological and physiological changes to the vastus lateralis after an anterior cruciate ligament (ACL) tear. However, it is unclear whether these alterations are limited to just the vastus lateralis or are more representative of widespread changes across the thigh musculature and/or if these changes precede reconstruction. The purpose of this study was to determine T1ρ relaxation time, a measure of extracellular matrix organization in muscle, and physiological cross-sectional area (PCSA) for muscles of the quadriceps and hamstrings of the ACL-deficient and contralateral limbs soon after ACL injury. Methods T1ρ and diffusion tensor magnetic resonance imaging were performed on both limbs of 10 participants after primary ACL tear (< 10 weeks). T1ρ relaxation time and PCSA were calculated for all muscles of the quadriceps and hamstrings. Shapiro-Wilks tests were performed to assess normality. Outcomes were compared between limbs for each muscle of interest with paired t-tests or Wilcoxon signed-rank tests with the alpha level set to 0.05. Results T1ρ relaxation times were significantly longer for the vastus lateralis (7.0%), rectus femoris (15.4%), and vastus intermedius (9.4%) of ACL-deficient limb; whereas, relaxation times were similar between limbs for all hamstring muscles. PCSA was smaller for the vastus lateralis (-19.6%), vastus intermedius (-20.9%), vastus medialis (-26.0%), and semitendinosus (-15.0%) of the ACL-deficient limb compared to the contralateral limb. Conclusions These results provide evidence that morphological and physiological alterations occur within multiple muscles of quadriceps but not the hamstrings prior to ACL reconstruction. Establishing these differences between the quadriceps and hamstrings suggests there is a differential response within the thigh musculature to an ACL injury, providing a framework for more targeted interventions.